Resistance Test of Aedes aegypti Mosquito Larvae Against Organophosphate Insecticides at Medan Selayang - Zahir Husni Lubis; Nurfadly Nurfadly (Universitas Muhammadiyah Sumatera Utara, 2020)
Aedes aegypti is the main vector in several diseases such as Dengue Hemorrhagic Fever (DHF).Various types of efforts to control Aedes aegypti were carried out to terminate the transmission chain by spraying (organizing) the organophosphate insecticide. The use of irrational insecticides causes an increase in esterase enzymes, giving rise to the resistance of Aedes aegypti to insecticides. The purpose of this study is to determine the resistance status of Aedes aegypti larvae to organophosphate insecticides in Medan Selayang. The type of research used in this study is descriptive research with cross-sectional methods, using 276 larvae of Aedes aegypti. The results of this study are mosquito larvae that are susceptible (sensitive) to organophosphate insecticides by 66.3%, while mosquito larvae that are tolerant (moderate resistance) of organophosphate insecticides are 33.7% and resistant (high resistance) mosquito larvae were not found. There is 33.7% of Aedes aegypti larvae are tolerant (moderate resistance) to organophosphate insecticides and resistant (high resistance) mosquito larvae were not found.